KEBIJAKAN PANGAN DI INDONESIA: ANTARA SWASEMBADA PANGAN DAN KECUKUPAN PANGAN - Syafiullah, Yunan (Jurnal Bestari, 2008)
Food security becomes requirement to reach politics security and economy security that will end to the national security in giving the stability of the people's activity. It does not mean that food security must be indicated by the abundant food stocks available, but food security may refer to the sufficient food of domestic need; the adequate food which is reachable and fairly distributed and having good quality. Thus, the access of food adequateness gives more emphasize on the food security, rather than its convenience. Furthermore, in maintaining food security regarding production aspect, convenience, consumption, cost, and nutrition in term of periode and region, the information related to this matter tend to be useful for the eritical plan, prediction, evaluation, and intervetion of food policy.